TASKS, PRINCIPLES AND DIRECTIONS OF ADMINISTRATIVE ACTIVITY OF THE MIGRATION POLICE DEPARTMENT OF THE NATIONAL POLICE OF UKRAINE (Bulletin of criminological association of Ukraine, 2024)
The article examines the essence of the areas of administrative activity of the migration police. The priority tasks of the unit are to ensure compliance with migration laws, control the movement of stateless persons and foreigners, and counteract human trafficking and illegal migration. In order to improve the efficiency of the Migration Police, a number of practical recommendations have been developed to expand the technical capabilities of this unit and deepen cooperation with the migration services of the European Union and other countries. As a result, it is logical and understandable that improving the technical base, based on the introduction of international experience of developed countries into the activities of the Migration Police of Ukraine, is a key component of the strategy for improving the efficiency of this body.
Keywords: migration; migration police; immigration; emigration; foreigners; stateless persons; human trafficking; artificial intelligence; international cooperation